Managing Fever Through Ayurvedic Therapeutic Diet (AYUSHDHARA, 2025)
Fever is a common symptom in many diseases and infections. People frequently resort to antipyretics and thereby suppress their immune system resulting in chronic low-grade inflammation in the long run. Body has the power to heal itself provided we are giving adequate support through therapeutic diet and fluid. According to Ayurveda Agni is deranged in Jwara which is responsible for all the associated symptoms. We can correct this Agni through therapeutic diet. In Ayurvedic text various Acharyas described countless therapeutic dietary preparations in the context of Jwara which have antipyretic effect, immunomodulatory effect and act by correcting the Agni. Such preparations mentioned in the classical textbooks of Ashtanga Sangraha, Sharngadhara Samhitha, Chakradutta, Chikitsamanjari, Bhavaprakasham and articles have been identified and listed in this literature review. People are reluctant to use such Ayurvedic therapeutic diet due to complexity in the preparation of these recipes and the limited availability of certain drugs. More clinical research should be done in the field of Ayurvedic nutraceuticals to overcome these limitations.